Persepsi Peternak Terhadap Pemanfaatan Hutan Desa Untuk Mendukung Usaha Peternakan di Desa Selorejo dan Desa Gadingkulon Kecamatan Dau Kabupaten Malang - Putri, Nabila Ananda; Azizah, Siti (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Wonokerto Lestari Village Forest, located at the foot of Mount Kawi with an area of 1,574.45 ha, is utilized by the entire community of Selorejo Village and Gadingkulon Village, Dau District, Malang Regency in the agriculture and livestock sectors. If it is not utilized as a sustainable forest function, it will cause forest degradation and deforestation. This study aims to determine the form and analyze the perceptions of community farmers in the use of Village Forest in supporting livestock businesses. The research was conducted using questionnaire interviews (qualitative) with purposive sampling and snowball sampling techniques on May 6 - June 28, 2024. The characteristics of the informants include farmers who have utilized the Village Forest area for their livestock business, as well as community groups authorized in the management of the Village Forest area. It is known that the form of utilization related to livestock business is by taking forage for livestock that grows wildly around the Village Forest land without further planting. Furthermore, the perception of the farming community towards the utilization of the Village Forest for livestock business is quite diverse, although it tends to be positive.